2017
DOI: 10.1002/mde.2850
|View full text |Cite
|
Sign up to set email alerts
|

Are risk disclosures an effective tool to increase firm value?

Abstract: The objective of this paper is to test the effect of risk disclosures on firm value. The results show that the disclosure of information on risks is positively associated with the value of a firm. In addition, our findings highlight that this association is mediated by corporate reputation, which improves for enhanced risk disclosure practices. This evidence is particularly important to understand the usefulness of the disclosure of information on risks in the dialogue between a firm and its stakeholders. Mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 71 publications
1
35
0
3
Order By: Relevance
“…Differently from some previous studies that provided evidence of positive correlation between improved NFI and financial performance [22][23][24][25], the multivariate regression used to test the hypothesis has provided evidence that there is no association between the preparation of NFI and the financial and market performance of the companies, both in the current year of first adoption (2017) as well as the following one (2018). Therefore, these findings provide a first evidence that the nonfinancial disclosure, for the companies that prepare it in a context of mandatory disclosure, does not entail directly observable advantages on the accounting-based variable of financial performance ROA and on the market-based one in Tobin's Q.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Differently from some previous studies that provided evidence of positive correlation between improved NFI and financial performance [22][23][24][25], the multivariate regression used to test the hypothesis has provided evidence that there is no association between the preparation of NFI and the financial and market performance of the companies, both in the current year of first adoption (2017) as well as the following one (2018). Therefore, these findings provide a first evidence that the nonfinancial disclosure, for the companies that prepare it in a context of mandatory disclosure, does not entail directly observable advantages on the accounting-based variable of financial performance ROA and on the market-based one in Tobin's Q.…”
Section: Discussionmentioning
confidence: 76%
“…In the literature, we can observe a further gap concerning the scarcity of empirical evidence about the potential benefits of the disclosure of NFI in the stakeholder perspective. In particular, the relationship between risk disclosures and firm value is underresearched, as the NFI literature mainly focuses on the motivations supporting the companies' decision to disclose [4,20,22].…”
Section: Introductionmentioning
confidence: 99%
“…The second gap is the limited availability of empirical evidence on the effects of corporate risk disclosures and the potential benefits of the disclosure of information on risks that is yet to be explored. In particular, the relationship between risk disclosures and firm value has been neglected in existing research, as the risk literature mainly focuses on the incentives question that is related to the motives for which companies decide to disclose (Bravo, 2017; Elshandidy et al, 2018; Leopizzi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the study of (Bravo, 2017) found that CRD increases investor expectations, which in turn leads to a better evaluation of the company's performance. This may increase the efficiency of investments.…”
Section: Literature On Risk Information Disclosurementioning
confidence: 99%